2016
DOI: 10.3389/fphar.2016.00325
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid Toxicity and Mitochondrial Susceptibility: A Novel Neurological Complication in a Lebanese Patient

Abstract: The recent rise in the use of linezolid to treat a variety of resistant pathogens has uncovered many side effects. Some patients develop lactic acidosis, myelosuppression, optic or peripheral neuropathies, and myopathies. We evaluated an elderly patient who presented to the Emergency Room with linezolid toxicity and a novel neurologic complication characterized by bilateral globi pallidi necrosis. Mitochondrial ribosome inhibition was described to be the predisposing factor. The patient belongs to the mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Substantial reduction of the cost occurred with the release of generic versions of linezolid at the end of 2015. Rare but serious neurological complications (optic and peripheral sensory neuropathies) have been reported with prolonged linezolid use and are more prevalent in subjects with preexisting neurological conditions, alcoholics, diabetics, or recipients of chemotherapeutic agents as was the case in our subject [ 12 15 ]. Duration but not the indication for linezolid use is the major determinant of neurological side effects, and studies have shown that optic neuropathies resolve after linezolid cessation, while peripheral neuropathies do not [ 12 ].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Substantial reduction of the cost occurred with the release of generic versions of linezolid at the end of 2015. Rare but serious neurological complications (optic and peripheral sensory neuropathies) have been reported with prolonged linezolid use and are more prevalent in subjects with preexisting neurological conditions, alcoholics, diabetics, or recipients of chemotherapeutic agents as was the case in our subject [ 12 15 ]. Duration but not the indication for linezolid use is the major determinant of neurological side effects, and studies have shown that optic neuropathies resolve after linezolid cessation, while peripheral neuropathies do not [ 12 ].…”
Section: Discussionmentioning
confidence: 77%
“…Other important side effects include myelosuppression (especially thrombocytopenia and rarely aplastic anemia) and type B lactic acidosis. [ 15 ]. These side effects appear to be mediated by direct mitochondrial protein synthesis inhibition by linezolid, and they disappear gradually after linezolid withdrawal [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its half-life is approximately double, which allows for once-daily dosing. Finally, it seems safer as, although TD is a more potent inhibitor of mitochondrial protein synthesis than linezolid, the risks of adverse effects related to mitochondrial dysfunction (i.e., lactic acidosis, myelosuppression, and neuropathy) were found to be inferior to those for linezolid in studies carried out in animal models [ 79 , 80 ]. TD is approved for the treatment of aSSTIs by the FDA [ 81 ] and EMA [ 82 ].…”
Section: Oral and Parenteral Antibioticsmentioning
confidence: 99%
“…One of the drugs suffering from poor water solubility and associated with an increased risk of mitochondrial toxicity is linezolid (LIN, Fig. 1), a wide-range antibiotics used mainly to treat infections caused by resistant strains of Gram-positive bacteria (Moellering, 2003;Abou Hassan et al, 2016). To date, crystal structures of two polymorphic forms of LIN are known, orthorhombic form II (Maccaroni et al, 2008), which is a commercially available form, and triclinic form III (Rao & Reddy, 2005;Tanaka & Hirayama, 2008), which is also mistakenly referred to in the literature as form IV (Wielgus et al, 2015).…”
Section: Introductionmentioning
confidence: 99%